Pen and ink drawing :a simple guide - Dunn, Alphonso (Woodland Park, New Jersey : Three Minds Press, 2015)
This book covers the essential aspects of pen and ink drawing and more. It explores basic materials and instruments; fundamental properties of strokes and pen control; key elements of shading; and indispensable techniques for creating vibrant textures. As a bonus, a chapter is devoted to what the author refers to as, the secret Line of Balance. This book is not just written to instruct but also to intrigue and inspire enthusiasts of pen and ink drawing.
Start-up -- Supplies : Ink and paper Common ink drawing instruments Unconventional instruments Additional supplies -- Strokes : Effective pen control Basic types of strokes Ways to vary a stroke Ways to use a stroke -- Shading : Seeing values Value scales Gradation of value Structure and shading Shading block forms Shading round forms Shading complex forms -- Simulating texture : Texture reference chart Realistic texture Texture follows form Texture on block forms Texture on spherical forms Texture on cylindrical forms Bringing it all together -- Sketchbooking : The sketchbook is your battlefield You can learn a lot by copying Thumbnails are invaluable You can always find things to draw Abstract drawing Gesture drawing The human figure Faces and portraits Animals Sketching scenery Develop your own drawing process Creating with new ideas -- Stages of a finished drawing : Stage 1: Composition and design Stage 2: Pencil underdrawing Stage 3: Inking -- Secret line of balance : The line of balance In patterns of nature Movement Drawing portraits Drawing the human figure Drawing animals Drawing plants and flowers -- Send-off.
Keywords: Pen drawing -- Technique; Drawing -- Study and teaching